Cyprinidae fish family in Batang Kerang floodplain, Balai Ringin, Serian, Sarawak - Salsabila, Binti Haji Abdul Wahid (Universiti Malaysia Sarawak, (UNIMAS), 2012)
A study on the Cyprinidae fish family had been carried out in Batang Kerang floodplain, Balai Ringin, Serian, Sarawak, during high and low water seasons. A total of 375 individual fish representing 23 species belonging to 8 families were identified. A total of 15 species of 7 families and 20 species of 7 families were collected during high and low water seasons respectively. Cyprinidae fish family (73.3%) were dominated the habitat for both seasons. The dominant species was Cyclocheilichlhys apogon. There were significant different of the physicochemical water parameters (p<0.05) such as pH, dissolved oxygen, water transparency and turbidity between both seasons.